Hodgkin lymphoma with granulomas. Demystifying the dilemma - Aggarwal, Phiza; Sharma, Mayank; Nimbran, Vinod; Kaur, Kamalpreet (Annals of Pathology and Laboratory Medicine, 2018)
Presence of granuloma in Hodgkin lymphoma is a common finding which is often a source of diagnostic confusion. There is no clearly defined strategy to approach this dual pathology. The present case describes a diagnostic approach using modalities like immunohistochemistry and Catridge based nucleic acid amplification test that helped reach to most likely cause of granuloma with underlying Hodgkin lymphoma. DOI:10.21276/APALM.1861